ANALISIS PERMASALAHAN KOPERASI BAITUL MAAL WA TAMWIL (KBMT) PERKOTAAN (Studi Kasus KBMT di Kota Bogor) - Khoirudin, Ahmad; Akbar, Nashr (IQTISHODUNA, 2016)
Microfinance as an effective tool provides financial service for those who do not have the accessor could not be accessed by a commercial bank or other financial institution. The Growth of Baitul Maal watamwil (BMT) as one of the Islamic financial institution is very fast and massive. There are many challengesand obstacles that inhibit the growth of it, either from internal or external of BMT. The purpose of this studyis to identify the issues faced by the urban of BMT (Bogor City), used Analytic Network Process (ANP). Thestudy also attempt to provide solution of the BMT problem faced. The result of this study showed that theproblem of internal Issues was more dominant than External Issues, with the priority level of 54%. Based onthe Internal Problems aspect, the dominant issue was the problem of â€œLow Quality and understanding ofHuman Resourceâ€. Meanwhile an aspect of the external problem is â€œthe strictness of Business Competitionâ€.Furthermore, the solution could be implemented are 1) Training for Human Recourse 2) BMT Mentoring bythe relevant government.